Aplikasi Asam Humat Untuk Mendukung Pertumbuhan Bibit Kopi Robusta (Coffea canephora) Pada Media Tanam Ultisol - Rosimarsela Rosimarsela; Nasamsir Nasamsir; Rudi Hartawan (Jurnal Media Pertanian, 2026)
Coffee is one of the plantation commodities that plays a fairly important role in economic activities. One type is robusta coffee, which until now is the type of coffee that dominates coffee plantations in Indonesia. One of the planting media that can be used for robusta coffee nursery activities is ultisol soil. The problem of low fertility in ultisol soil can inhibit seedling growth. The addition of humic acid is needed to improve soil structure and fertility, and can help in the absorption of nutrients needed by plants. This study aims to obtain the best dose of humic acid to support the growth of robusta coffee seedlings in ultisol planting media. This study was carried out for 3 months starting from May - August 2024. This research was conducted on Jl. Rajawali, Kenali Besar, Kec. Kota Baru, Jambi City. The environmental design used in this study was a Completely Randomized Design (CRD) with one treatment factor, namely humic acid (g polybag-1) consisting of 6 different treatments, namely a0 (control), a1 (5 g), a2 (10 g), a3 (15 g), a4 (20 g), a5 (25 g). Each treatment was repeated 4 times, so that 24 experimental units were obtained. Each experimental unit consisted of 4 plants consisting of 3 sample plants and 1 reserve plant, so that the total was 96 plants. The results showed that humic acid treatment had a significant effect on stem diameter, total leaf area, dry weight of the crown, dry weight of the roots, water content of the media, and the quality index of robusta coffee seedlings. However, this treatment had no significant effect on plant height and number of leaves of robusta coffee seedlings on ultisol planting media. The administration of humic acid in treatment a3 (15 g) can increase the growth of stem diameter by 5.16%, dry weight of the crown by 7.56%, dry weight of the roots by 21.05%, and seedling quality index by 6.57%, compared to without treatment (control).